PENGARUH STRATEGI PENETAPAN HARGA, KUALITAS PRODUK DAN PELAYANAN TERHADAP PENINGKATAN PENJUALAN PADA APOTEK KIMIA FARMA DI MARISA KABUPATEN POHUWATO - Sulaiman; Sulerski Monoarfa (Melati Institute, 2023)
The research objectives were: Analyzing the effect of pricing strategies, products and services both partially and simultaneously on increasing sales at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency. Data analysis methods to solve problems are used multiple regression analysis, correlation and significance tests. The results of hypothesis testing both partially and simultaneously in research at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency, the results obtained are: a) The selling price setting strategy has a partially positive and significant effect on increasing sales at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency. b) Product quality has a partially positive and insignificant effect on increasing sales at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency. c) Service quality has a partially positive and insignificant effect on increasing sales at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency. d) The selling price setting strategy, product quality and service quality simultaneously have a positive and significant effect on increasing sales at the Kimia Farma Pharmacy in Marisa, Pohuwato Regency. Thus the results of data analysis or discussion are in line with the research hypothesis.